ANALISIS USAHA DAN NILAI TAMBAH PENGOLAHAN MARNING JAGUNG (Studi Kasus di Kelurahan Loa Janan Ulu Kecamatan Loa Janan Kabupaten Kutai Kartanegara) (Analysis of Business and Added Value of Corn Marning Processing (Case Study in Loa Janan Ulu Urban Village Loa Janan Subdistrict Kutai Kartanegara District)) - MAHDALENA AYU SAPUTRI; RITA MARIATI (Universitas Mulawarman (University of Mulawarman), 2020)
The aims of this research were to know the production cost, revenue, income, and added value in processing business of corn marning in the Urban Village of Loa Janan Ulu, Subdistrict of Loa Janan, District of Kutai Kartanegara. This research was conducted in November 2018 until January 2019. The data analysis were done to count the production cost, revenue, income, and added value. The results of research showed that the producation cost of corn marning in the Urban Village of Loa Janan Ulu, Subdistrict of Loa Janan, District of Kutai Kartanegara was IDR30,001,160.40 month-1, whereas revenue of IDR42,392,000.00 month-1, and income of IDR12,390,839.60 month-1. The added value of corn marning processing was IDR11,716.07 kg-1 with a ratio of 44.91%.